Wages and employment of French workers with African origin - Romain Aeberhardt; Denis Fougère; Julien Pouget; Roland Rathelot (Institute for the Study of Labor (IZA), 2007)
Our study proposes an econometric decomposition of the wage gap and of the difference in employment probabilities between French workers whose both parents had French citizenship at birth and French workers whose at least one parent had the citizenship of an African country at birth. For that purpose, we use data coming from the Formation Qualification Professionnelle (FQP) survey conducted by INSEE (Paris) in 2003. Our study is the first to estimate both employment and wage differentials between native French workers and children of African migrants. We find that one half of the employment gap and one third of the wage gap is not explained by differences in observable covariates between the two groups. This result is obtained by using a new method yielding more precise results when the sample size of the potentially discriminated group is small.
Keywords: 330; Lohndifferenzierung; Ethnische Diskriminierung; Afrikaner; Frankreich